Muscular fitness, adherence to the Southern European Atlantic Diet and cardiometabolic risk factors in adolescents (2017)
Background and Aim Muscular fitness and an adherence to the Southern European Atlantic Diet (SEADiet) have been inversely associated with cardiometabolic risk. Our aim was to assess the independent and combined associations of muscular fitness and adherence to the SEADiet on cardiometabolic risk in adolescents. Methods and Results A total of 467 Portuguese adolescents (275 girls) participated in this cross-sectional study. Sum of the Z-Scores of Curl-Up and Push-Up tests was used to create a muscular fitness score. Adherence to SEADiet was obtained using a food frequency questionnaire. A cardiometabolic risk score was computed from sum of Z-score of triglycerides, systolic blood pressure, total cholesterol/HDL ratio, HOMA-IR and waist circumference. Adolescents with low muscular fitness and low adherence to the SEADiet had the poorest cardiovascular profile F(5, 452) = 5.074 (p and lt; 0.001) and the highest odds of having a high cardiometabolic risk score (OR = 4.5; 95% CI: 2.1–14) when compared to those with High muscular fitness/High adherence to the SEADiet after adjustments for age, sex, pubertal stage, socioeconomic status, total energy intake, low-energy reporter and cardiorespiratory fitness. Conclusions Our findings seem suggest that improving muscular fitness as well as an adherence to the SEADiet could be an important strategy to reduce clustered cardiometabolic risk in youth. © 2017 The Italian Society of Diabetology, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition, and the Department of Clinical Medicine and Surgery, Federico II University